Burnout among medical students and young doctors in Poland: Risk factors and preventive strategies: a review of current literature - Karbowiak, Krzysztof; Nawrat, Natalia; Makselan, Natalia; Wijas, Daniel; Kozdra, Bartłomiej; Kluś, Michał; Olszok, Mikołaj; Handzel, Karolina; Anczyk, Antoni (Quality in Sport, 2026)
Background: Burnout among medical students and young doctors is an increasing occupational concern. Defined in ICD-11 as a syndrome resulting from chronic, unsuccessfully managed workplace stress, it is particularly relevant in healthcare systems facing staff shortages, heavy workloads, and organizational instability. These pressures are also visible in Poland. Objective: To synthesize current evidence (2020–2025) regarding prevalence, risk factors, consequences, and preventive strategies related to burnout among medical students and early-career physicians, with attention to the Polish context. Methods: A narrative review of peer-reviewed literature published between 2020 and 2025 was conducted using PubMed/MEDLINE, Scopus, and Web of Science. Included studies comprised original research, systematic reviews, meta-analyses, and randomized trials examining burnout in medical students, residents, and junior doctors. Findings were analyzed qualitatively, prioritizing higher-level evidence for intervention assessment. Results: Organizational factors-high workload, long hours, staffing deficits, administrative burden, and hierarchical culture-emerge as primary drivers of burnout. Psychological traits such as maladaptive perfectionism and empathic distress increase vulnerability but are secondary to structural determinants. Burnout is strongly associated with depression, anxiety, substance use, and elevated risk of medical errors and reduced patient safety. Polish data indicate substantial distress and burnout, particularly during the COVID-19 period. Individual interventions, including mindfulness-based programs, show modest effects, whereas mentoring, coaching, and organizational reforms targeting workload and leadership demonstrate stronger impact. Conclusions: Burnout in Polish medical trainees is predominantly system-driven. Sustainable reduction requires structural and organizational change alongside supportive individual-level strategies.